Bacterial outer membrane vesicles, a potential vaccine candidate in interactions with host cells based - Wei Cai; Dinesh Kumar Kesavan; Jie Wan; Mohamed Hamed Abdelaziz; Zhaoliang Su; Huaxi Xu (Diagnostic Pathology, 2018)
Abstract Both Gram-Positive and Gram-Negative bacteria can secrete outer membrane vesicles (OMVs) in their growth and metabolism process. Originally, OMVs were considered as a by-product of bacterial merisis. However, many scientists have reported the important role of OMVs in many fields recently. In this review, we briefly introduce OMVs biological functions and then summarize the findings about the OMVs interactions with host cells. At last, we will make an expectation about the prospects of the application of OMVs as vaccines.